1977
DOI: 10.1104/pp.60.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethylene on the Endogenous Cytokinin and Gibberellin Levels in Tuberizing Potatoes

Abstract: High concentrations of 2-chloroethylphosphonic acid inhibited tubenzation on aged potato tubers (Solanum tuberosum) that had been predisposed to the little tuber disorder. As a result of this treatment sprouts developed which contained relatively high levels of endogenous gibberellins and which elongated normally. The endogenous cytokinin levels in the different treatments did not change appreciably. It is suggested that tuberization is prevented by ethylene either as a direct inhibition of cell division or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[14,15] . Dimalla and Van Staden [5] reported that ethylene prevented 'little-tuber disorder', i.e ., the formation of small tubers on aged mother tubers . Palmer and Barker [17] and Koda and Okazawa [10] noticed diageotropic growth of shoots after treatment with ethylene in vitro, but they found no effect on tuberization .…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] . Dimalla and Van Staden [5] reported that ethylene prevented 'little-tuber disorder', i.e ., the formation of small tubers on aged mother tubers . Palmer and Barker [17] and Koda and Okazawa [10] noticed diageotropic growth of shoots after treatment with ethylene in vitro, but they found no effect on tuberization .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue sensitivity to cytokinins is important for the regulation of dormancy, as an increase in both cytokinin content and sensitivity appear to be the principal factors leading to the loss of dormancy (Turnbull and Hanke, 1985;Suttle, 2004b). Cessation of meristematic activity in potato stolon apex during tuberization has been reported (Burton, 1989) and this can be orchestrated by ethylene inhibition of the action of cytokinins (Dimalla and van Staden, 1977). It is therefore possible that exogenous Changes in the level of the plant growth regulator abscisic acid (ABA) in sweetpotato in relation to the dormancy mechanism has not been reported previously.…”
Section: Hormonal Changes and Sprout Growthmentioning
confidence: 99%